Understanding factors affecting Chinese medical staff's fear of receiving the fourth dose of COVID-19 vaccine: A cross-sectional study in Taizhou - Li-Li Huang; Wei-Wen Hong; Wei-Wei Hu; Xian-Hua Guan; Yan-Hong Jiang (Taylor & Francis Group, 2023)
ABSTRACTThe study was conducted to assess medical staffs' fear of receiving the fourth dose of the Coronavirus disease 2019 (COVID-19) vaccine. From December 17, 2022, to January 31, 2023, an online survey was conducted to assess the fear among medical staffs regarding the administration of the fourth dose of the COVID-19 vaccine. The participants were exclusively drawn from a tertiary grade hospital in Taizhou. Out of the 1, 832 medical staffs invited to participate in the questionnaire, a total of 613 (33.5%) provided valid responses for subsequent analysis. Among them, 81 (13.8%) expressed fear of receiving the fourth dose of COVID-19. The fear was significantly influenced by these factors: the presence of serious food/drug allergic reactions (OR = 3.84, 95% CI: 1.40-10.52), received booster COVID-19 vaccine (OR = 0.20, 95% CI: 0.11-0.35), opinion on vaccination requirement (OR = 0.20, 95% CI: 0.11-0.35), viewpoint (OR = 0.23, 95% CI: 0.12-0.44) with scores ≥10, and positive attitude toward vaccination (OR = 0.21, 95% CI: 0.13-0.35). Our study revealed that a subset of medical staffs still harbor apprehension toward receiving the fourth dose of the new COVID-19 vaccine. Factors influencing this fear encompass allergic reactions, booster COVID-19 vaccine, as well as opinion, viewpoint, and attitude toward vaccination. Educating medical staffs on these factors may help mitigate their fear.